Pengaruh Model Pembelajaran Make a Match Berbantuan Media Diorama Terhadap Hasil Belajar Peserta Didik Pada Materi Siklus Air Di Kelas V SDN 62 Banda Aceh - Ulfia, Ulfia; Safiah, Intan; Fitriani, Suci (Universitas Syiah Kuala, 2022)
This study entitled The Effect of Make A Match Learning Model Assisted by Diorama Media on Student Learning Outcomes on Water Cycle Material in Class V SDN 62 Banda Aceh. The formulation of the problem in this study is